2018
DOI: 10.1186/s12889-018-5231-1
|View full text |Cite
|
Sign up to set email alerts
|

Disparities in tobacco use by adolescents in southeast, Nigeria using Global Youth Tobacco Survey (GYTS) approach

Abstract: BackgroundTobacco use during adolescence is a substantial problem and adolescents are at higher risk of addiction and prolonged use. To reduce the burden of tobacco-related morbidity and mortality, monitoring of adolescent tobacco use is imperative. We aimed to determine the prevalence of tobacco use among adolescents in urban and rural secondary schools in Enugu State, southeast Nigeria.MethodsA cross-sectional study of 4332 adolescents in 8th to 10th grades in 25 urban and 24 rural secondary schools in Enugu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 30 publications
(29 reference statements)
1
17
5
Order By: Relevance
“…Therefore, results from this study need to be confirmed in a longitudinal study. Secondly, smoking in previous studies was defined as “smoking 1 day or more within the past 30 days” or “smoking 1 cigarette or more within the past 7 days” [ 46 , 47 ]. However, smoking in this study was defined as “a history of smoking more than 100 cigarettes during the participant’s lifetime”, which is consistent with other previous studies but may underestimate the true prevalence of smokers [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, results from this study need to be confirmed in a longitudinal study. Secondly, smoking in previous studies was defined as “smoking 1 day or more within the past 30 days” or “smoking 1 cigarette or more within the past 7 days” [ 46 , 47 ]. However, smoking in this study was defined as “a history of smoking more than 100 cigarettes during the participant’s lifetime”, which is consistent with other previous studies but may underestimate the true prevalence of smokers [ 28 , 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Details of the study design and procedure have been described elsewhere 15 . In brief, this study was carried out in urban and rural secondary schools in Enugu State, southeastern Nigeria, using the Global Youth Tobacco Survey (GYTS) design.…”
Section: Study Design Participants and Proceduresmentioning
confidence: 99%
“…A sample of 80 students was sought in each school, corresponding to 2000 students per stratum. A pretested self-administered questionnaire (Supplementary file) adapted from GYTS Core Questionnaire 15,16 was used to collect data without identifiers, from November to December, 2015.…”
Section: Study Design Participants and Proceduresmentioning
confidence: 99%
“…Seven articles measured tobacco or cigarette use (Arute et al, 2015;Chinawa et al, 2014;Itanyi et al, 2018;Odukoya et al, 2013;Okagua et al, 2016;Raji et al, 2018), one article measured both alcohol and tobacco use (Olugbenga-Bello et al, 2014), and eight studies measured the use of any of alcohol, tobacco, cocaine and cannabis as psychoactive substance use (Alex-Hart et al, 2015;Atoyebi & Atoyebi, 2013;Famuyiwa et al, 2011;Idowu et al, 2018;Igwe, 2009;Manyike et al, 2016;Ogunsola & Fatusi, 2017;Oshodi et al, 2010).…”
Section: Psychoactive Substances Measured In the Studiesmentioning
confidence: 99%
“…Four authors used a modified World Health Organization (WHO) Student Drug Use questionnaire as their data collection tool (Igwe, 2009;Manyike et al, 2016;Ogunsola & Fatusi, 2017;Oshodi et al, 2010). Four authors used the Global Youth Tobacco Survey questionnaire to collect data on tobacco consumption (Itanyi et al, 2018;Odukoya et al, 2013;Okagua et al, 2016;Raji et al, 2013). One author used the Health Kids Colorado Questionnaire (Chinawa et al, 2014).…”
Section: Data Collection Instrumentsmentioning
confidence: 99%